PERAN SOLUTION-FOCUSED PREMARITAL COUNSELING TERHADAP KESIAPAN MENIKAH PASANGAN INDIVIDU DEWASA MUDA - Rebeka Pinaima; Elmira N. Sumintardja (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2016)
Couples who are going to get married tend to prepare intensively for their wedding, but most invest little time preparing for their marriage, which is intended to last a lifetime. As a result, the couple might lack having marital readiness to face potential problems that could arise in marriage. This applied study attempts to learn about the role of solution-focused premarital counseling as an intervention to optimize young adult couples’ marital readiness. Data were collected from 10 participants (five young adult couples) between age 25-29 (mean = 26.70, SD = 1.49) from Jakarta. Wilcoxon Signed Ranks Test using SPSS 23 are applied. Results showed that solution-focused premarital counseling increased each couples’ marital readiness in general, which includes the family of origin factor, significant others approval, and the couple interactional processes. The program enabled all participants to receive deeper knowledge about their partners and understand the impact of each family background. It also trained each couples to establish their skills and different strategies to meet conflict resolution. However, there were no significant improvement on the individual characteristics factor, possibly caused by the relatively short period of the intervention.